Knowledge Sharing In Public Sector Case Study: Ministry Of Labor In Republic Of Kazakhstan - Mynbayev, Serik M (2010)
This research purposes at investigating the role of particular factors in organizational culture in the outcome of knowledge sharing. Such factor as trust, mutuality between staff, rewards and management support play an important role in describing the relationships between staff and sequentially, providing possibilities to break barriers to knowledge sharing. Another focus in this study is potential individual and organizational barriers to knowledge sharing. A number of criteria including the result of organizational environment on personal attitudes of knowledge sharing are considered in this research as well.